2013
DOI: 10.3233/jad-122098
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Long-Term (5 Years) Conversion to Dementia Using Neuropsychological Tests in a Memory Clinic Setting

Abstract: The use of neuropsychological tests to detect cognitive decline in the initial phases of Alzheimer's disease (AD) has faced significant limitations, namely the fact that most cohort studies of conversion to dementia had relatively short follow-up periods. The aim of the present study is to assess the predictive value for future conversion to dementia of a comprehensive neuropsychological battery applied to a cohort of non-demented patients followed-up for 5 years. Participants (n = 250) were selected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…We are able to predict conversion to dementia within a long-time span (5 years). Indeed, using neuropsychological data to detect cognitive decline in initial phases of AD has faced significant limitations, due to the short follow-up periods which characterize most cohort studies of conversion to dementia [24, 28, 31, 46]. Our work supports the view that longer follow-ups might be an asset in the study of conversion to dementia, as the best results were achieved with the longest windows used.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We are able to predict conversion to dementia within a long-time span (5 years). Indeed, using neuropsychological data to detect cognitive decline in initial phases of AD has faced significant limitations, due to the short follow-up periods which characterize most cohort studies of conversion to dementia [24, 28, 31, 46]. Our work supports the view that longer follow-ups might be an asset in the study of conversion to dementia, as the best results were achieved with the longest windows used.…”
Section: Discussionsupporting
confidence: 59%
“…NPTs are relatively inexpensive and non-invasive, can be readily obtained in most clinical settings [23, 24], are required for diagnosis purpose and have proven their value in tracking the cognitive decline in dementia [8]. Still, their predictive power has not been fully exploit, as it has been addressed mostly by classical statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the observation that neuropathological changes start in brain circuits subserving memory formation and consolidation, many studies identified memory deficits as an early predictor of conversion to AD dementia (Albert et al 2001;Tabert et al 2006;Silva et al 2013). Further, studies also reported subtle deficits in non-memory domains in individuals with prodromal AD, such as insufficiencies in executive functioning (Albert et al 2001;Rapp & Reischies, 2005), verbal fluency (Fabrigoule et al 1998;Laukka et al 2004), attention (Linn et al 1995;Nielsen et al 1999), and global cognitive functioning (Backman & Small, 1998;Fabrigoule et al 1998).…”
Section: Introductionmentioning
confidence: 77%
“…One of the hallmarks of amnestic MCI and AD is significant verbal memory impairment . There are several neuropsychological tests for memory and learning assessment, such as the logical memory (LM) test, the verbal paired‐associate learning (VPAL) test, and the California verbal learning test (CVLT) . Impairment in LM test has been shown to be associated to higher risk of conversion to AD, although impairment in CVLT revealed better overall accuracy in distinguishing MCI from normal aging .…”
Section: Single‐source Data Analysismentioning
confidence: 99%